2019
DOI: 10.3889/oamjms.2019.452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fixation Methods for Preservation Cytology Specimens of Cell Block Preparation Using 10% Neutral Buffer Formalin and 96% Alcohol Fixation in E-cadherin and Ki-67 Immunohistochemical Examination

Abstract: BACKGROUND: Cytological and molecular examinations are among the most important examinations in cancer diagnosis. 96% alcohol is a fixative solution commonly used by clinicians for cytological samples because of its accessibility and affordability. Cellblock preparation from cytology specimen may increase morphology detail and may be used for further biomarker analysis. E-cadherin is an adhesion protein expressed in the cell membrane of most carcinoma. Ki67 is a protein expressed in nuclei of malignant cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In other cell models, formaldehyde or alcohol-based fixatives (including methanol) have alternatively been used for the immunofluorescence detection of claudin 1 18,20,21 or E-cadherin. 22,23 Interestingly, the direct comparison of different fixing protocols including formaldehyde and methanol fixation for the detection of claudin 1 in airway epithelial cells concluded that methanol fixation was optimal to obtain consistent and reliable signals. 24 Altogether, these observations strongly suggest that the best fixation method depends on the sample type, cell type, or experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell models, formaldehyde or alcohol-based fixatives (including methanol) have alternatively been used for the immunofluorescence detection of claudin 1 18,20,21 or E-cadherin. 22,23 Interestingly, the direct comparison of different fixing protocols including formaldehyde and methanol fixation for the detection of claudin 1 in airway epithelial cells concluded that methanol fixation was optimal to obtain consistent and reliable signals. 24 Altogether, these observations strongly suggest that the best fixation method depends on the sample type, cell type, or experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Cell block section is an ideal sample type to perform immunocytochemical study because the sample processing is similar to that of histologic section. [21][22][23] However, when cell block is not available, ER and PR can be tested on Papanicolaou-stained smear as long as in-house validation has been performed (Fig. 4).…”
Section: Prognostic/predictive Markersmentioning
confidence: 99%
“…12,13 It is known that differences in fixation and preparation of cytology compared to biopsies may affect the results of IHC. [14][15][16] Only a few studies have included a limited number of mesotheliomas with paired biopsies and effusion cytology specimens for comparison of protein expression by IHC. [17][18][19][20][21][22] In a previous study, we showed that IHC assessment of PD-L1 in paired specimens from pleural mesotheliomas is comparable, but we found a higher concordance between biopsies and effusions in epithelioid than in non-epithelioid mesotheliomas, 23 which may indicate biological differences.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that differences in fixation and preparation of cytology compared to biopsies may affect the results of IHC 14–16 . Only a few studies have included a limited number of mesotheliomas with paired biopsies and effusion cytology specimens for comparison of protein expression by IHC 17–22 .…”
Section: Introductionmentioning
confidence: 99%